2008
DOI: 10.1158/1541-7786.mcr-07-0297
|View full text |Cite
|
Sign up to set email alerts
|

Role of Activating Transcription Factor 3 on TAp73 Stability and Apoptosis in Paclitaxel-Treated Cervical Cancer Cells

Abstract: Taxol (paclitaxel) is a potent anticancer drug that has been found to be effective against several tumor types, including cervical cancer. However, the exact mechanism underlying the antitumor effects of paclitaxel is poorly understood. Here, paclitaxel induced the apoptosis of cervical cancer HeLa cells and correlated with the enhanced activation of caspase-3 and TAp73, which was strongly inhibited by TAp73β small interfering RNA (siRNA). In wild-type activating transcription factor 3 (ATF3)–overexpressed cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 44 publications
2
21
0
Order By: Relevance
“…Our study showed that the cell death inducing mechanism by hGal9 uses ATF3, a member of the ATF/CREB family of transcription factors that functions as a tumor suppressor (25)(26)(27)(28)(29), but not p53 or Bim, the major proapoptotic factors in cell death induced by conventional genotoxic agents or Bcr-Abl TKIs. This implies that hGal9 is effective against CML cells that have lost their addiction to Bcr-Abl TK activity or their functional p53.…”
Section: Discussionmentioning
confidence: 78%
“…Our study showed that the cell death inducing mechanism by hGal9 uses ATF3, a member of the ATF/CREB family of transcription factors that functions as a tumor suppressor (25)(26)(27)(28)(29), but not p53 or Bim, the major proapoptotic factors in cell death induced by conventional genotoxic agents or Bcr-Abl TKIs. This implies that hGal9 is effective against CML cells that have lost their addiction to Bcr-Abl TK activity or their functional p53.…”
Section: Discussionmentioning
confidence: 78%
“…The incomplete suppression of apoptosis by the p53 shRNA might be due to the residue p53, effects of ATF3 on p53-independent E6 functions (e.g. repression of pro-apoptotic Bak and Bax) (8,9), or ATF3-mediated activation of other p53 family members such as p73 (33). We therefore concluded that ATF3 can activate p53 and promote p53-mediated cell cycle arrest and apoptosis in HPV-positive cells.…”
Section: Atf3 Directlymentioning
confidence: 81%
“…Taxol shows great efficacy against malignant tumors especially in cervical, breast, and ovarian cancer [1,2]. Taxol acts by binding to tubulin and by promoting its assembly into microtubules.…”
Section: Introductionmentioning
confidence: 99%